Metaphysics and Science nowadays - AKA, Pancrace; KOUADIO, Franck (Revue Internationale du Chercheur, 2025)
Abstract Life is underpinned by the silent weaving of Metaphysics. In its full and complete expression, the latter is rhythmic and harmoniously sewn with the unbreakable thread of the former. Metaphysics is that which is beyond the physical, but also that which, to be supraphysical, constitutes the physical in its essential form. There is therefore, in man, just as in life and in science, a metaphysical root which gives them essence, meaning, existence and consistency. Knowledge contains, implicitly, the secret design of the frantic quest for the metaphysical root of life and man. A metaphysical object by nature, man becomes the subject par excellence of the science of being in general which is Metaphysics. The latter implies particular sciences which deal with particular beings. This draft article theorizes, in an analytical and historical-critical approach, the undeniable and inescapable link between Metaphysics and Science. Better still, it questions the scientific nature, meaning, and relevance of metaphysics in this era of digital and technological revolution.